Site-Selective Suzuki–Miyaura Cross-Coupling Reactions of the Bis(triflate) of Methyl 3,7-Dihydroxy-2-naphthoate - Khaddour, Zien; Eleya, Nadi; Akrawi, Omer A.; Hamdy, Aws M.; Patonay, Tamás; Villinger, Alexander; Langer, Peter (Synlett, 2013)
Arylated naphthalenes were prepared by Suzuki–Miyaura reactions of the bis(triflate) of methyl 3,7-dihydroxy-2-naphthoate. The reactions proceeded with very good site-selectivity in favor of the sterically less hindered position 7, despite the proximity of position 3 to the electron-withdrawing ester group which plays a decisive role for the site-selectivity of Suzuki–Miyaura reactions of related substrates.
Keywords: catalysis; palladium; Suzuki–Miyaura reaction; naphthalenes; site-selectivity